Họ nguyên hàm của hàm số $f(x)=3x\left(x-\mathrm{e}^x\right)$ là
$x^3+(3x-1)\mathrm{e}^x+C$ | |
$x^3-3(x-1)\mathrm{e}^x+C$ | |
$x^3+3(x-1)\mathrm{e}^x+C$ | |
$x^3-(3x+1)\mathrm{e}^x+C$ |
Chọn phương án B.
Đặt $\begin{cases}
u=x\\ v'=\mathrm{e}^x
\end{cases}\Rightarrow\begin{cases}
u'=1\\ v=\mathrm{e}^x.
\end{cases}$
Khi đó $$\begin{aligned}
\displaystyle\int f(x)\mathrm{\,d}x&=\displaystyle\int\left(3x^2-3x\mathrm{e}^x\right)\mathrm{\,d}x\\
&=x^3-3\left(x\mathrm{e}^x-\displaystyle\int\mathrm{e}^x\mathrm{\,d}x\right)\\
&=x^3-3\left(x\mathrm{e}^x-\mathrm{e}^x\right)+C\\
&=x^3-3(x-1)\mathrm{e}^x+C.
\end{aligned}$$